Classical mechanics - Chow, Tai L. (New York : John Wiley and Sons, 1995)
This book is about: Kinematics of particle motion; The newtonian formulation of mechanics; Central force motion; Linear oscillations; ...
Keywords: Mechanics; Mechanics